PENGARUH ARUS KAS OPERASI TERHADAP PERTUMBUHAN LABA PERUSAHAAN PADA PT PEGADAIAN (PERSERO) KANWIL 1 MEDAN - Novien Rialdy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
ABSTRAKThe purpose of this research is to examine and determine the effect of operating cash flow to corporate earnings growth at P7'. Pegadaian (Persero) Kanwil I Medan. The method used in this resea•ch was quantitative descriptive method, the type of data used was quantitative data.The result of this research that there was significant influence of operating cash flow to earnings growth of company at PT. Pegadaian (Persero) Kanwil I Medan. Based on testing deiermination known that cash flow had an influence equal to 52.6% to profit growth.Keywords: Operating Cash Flow, Net Income, and Profit Growth